Relationship Between Posttraumatic Stress Disorder and Sleep Quality in Pregnant Earthquake Survivors - Öztaş, Hatice Gül; Aksüt Akçay, Emine; Erdī, Gülnaz (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
This study aims to investigate the relationship between posttraumatic stress disorder (PTSD) and sleep quality among pregnant earthquake survivors. A cross-sectional study was designed. The sample consisted of 272 pregnant earthquake survivors who were admitted to a hospital in southern Türkiye. Data were collected using “The Personal Information Disclosure Form,” “The Impact of Event Scale (IES),” and the “Pittsburgh Sleep Quality Index (PSQI)”. Statistical analyses included descriptive statistics, independent samples t-test, one-way ANOVA, Pearson correlation, and multiple linear regression.The mean IES total score was 41.37±19.73. The mean scores for the IES subscales were: Intrusion 15.17±8.19, Avoidance 15.25±6.74, and Hyperarousal 10.95±6.40. Considering the diagnostic cut-off value of 33 for PTSD on the IES, the mean IES score among the pregnant women in this study (41.37±19.73) indicates that their PTSD levels were above average and they were found to be at risk for PTSD. In general, positive, significant, but weak correlations were observed between the scale scores. A non-significant, positive, and very weak correlation was found between the IES and PSQI total scores (p>0.05).Pregnant earthquake survivors exhibited elevated PTSD levels and poor sleep quality. Although the association between PTSD and sleep quality was weak, the findings highlight the need for psychological screening and supportive interventions in antenatal care following disasters.
Keywords: Stress Disorders; Post-Traumatic; Earthquakes; Midwifery